2022
DOI: 10.1111/iwj.13785
|View full text |Cite
|
Sign up to set email alerts
|

The effects of virtual reality technology on reducing pain in wound care: A meta‐analysis and systematic review

Abstract: Virtual reality (VR) technology has been widely used in clinical nursing care in recent years. We aimed to systematically evaluate the effect and safety of VR technology on pain control in wound care, to provide evidence and support for clinical wound care. We searched PubMed, EMBASE, Cochrane Library, Web of Science, CINAHL, China Biomedical Literature Database, China National Knowledge Infrastructure (CNKI), Wanfang Data Knowledge Service Platform, and Chinese Science and Technology Journal databases for ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
(72 reference statements)
0
5
0
3
Order By: Relevance
“…Beberapa literatur telah mengulas penggunaan teknologi VR sebagai metode yang sangat efektif serta digunakan dalam tata laksana untuk mereduksi nyeri pada saat penggantian balutan luka dan juga terbukti aman (Ding et al, 2019;Elrazek & Hassan, 2019;He et al, 2022;Hoffman et al, 2019;Indovina et al, 2018;Theingi et al, 2021). Meskipun demikian, studi yang mengarah pada penggunaan teknologi virtual reality sebagai tata laksana untuk mereduksi nyeri pada pasien dewasa pasca bedah ORIF fraktur ekstremitas bawah saat tindakan penggantian balutan luka belum ditemukan.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Beberapa literatur telah mengulas penggunaan teknologi VR sebagai metode yang sangat efektif serta digunakan dalam tata laksana untuk mereduksi nyeri pada saat penggantian balutan luka dan juga terbukti aman (Ding et al, 2019;Elrazek & Hassan, 2019;He et al, 2022;Hoffman et al, 2019;Indovina et al, 2018;Theingi et al, 2021). Meskipun demikian, studi yang mengarah pada penggunaan teknologi virtual reality sebagai tata laksana untuk mereduksi nyeri pada pasien dewasa pasca bedah ORIF fraktur ekstremitas bawah saat tindakan penggantian balutan luka belum ditemukan.…”
Section: Pendahuluanunclassified
“…Selain itu, He et al, (2022) menemukan bahwa teknologi VR efektif mereduksi derajat dan sensasi nyeri selama perawatan luka dan dapat dijadikan metode non obat untuk mengatasi nyeri selama perawatan luka. Kemudian studi yang juga sesuai dengan penelitian ini yaitu penelitian Indovina et al, (2018) yang berfokus pada studi klinis untuk mengevaluasi kegunaan potensial dari virtual reality sebagai intervensi pendukung pada pasien selama menjalani prosedur medis yang menyakitkan dan penuh stres, melaporkan bahwa virtual reality merupakan suatu alat canggih yang menggunakan pendekatan distraksi yang memanfaatkan media secara audiovisual.…”
Section: Penerapan Teknologi Virtual Reality Terhadap Reduksi Perilak...unclassified
See 1 more Smart Citation
“…17 Studies have shown that VR is an effective drug-free method, which can be used for pain relief during wound care, effectively reducing the pain level of patients. 18 It has been shown to reduce anxiety during medical procedures in patients receiving a wide variety of treatments. 6 The increase in the number of studies on VR over the years makes it difficult to dominate the field and reveals the necessity of determining the trends and gaps in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, We read with great interest the review by He et al 1 about the effects of virtual reality technology on reducing pain in wound care. We highly appreciate their contribution to this important topic.…”
mentioning
confidence: 99%